Do Structural Changes of the Foot Influence Plantar Pressure Patterns During Various Stages of Pregnancy and Postpartum?. Issue 6 (December 2017) - Ramachandra, Preetha; Kumar, Pratap; Kamath, Asha; Maiya, Arun G.
Background . The foot of a pregnant woman undergoes morphological changes with the advancement of pregnancy. It is important to understand the structural changes of the foot during pregnancy and postpartum because any such change may alter the plantar pressure pattern and the entire foot biomechanics. Method . Primigravidae with a gestational age of 12 weeks or less, aged between 18 and 35 years were included in the study. They were prospectively studied across 5 time periods during pregnancy and postpartum. The measures recorded were length, width, navicular height, truncated foot length and normalized navicular height, truncated ratio of the foot, and the static plantar pressure pattern. Repeated-measures ANOVA was done to analyze the changes across various time periods. Results . All the foot parameters, except foot length and truncated foot length, showed significant differences across various time periods of pregnancy and postpartum (P < .001). It was found that the static plantar pressures also varied significantly (P ≤ .001).The maximum pressure was recorded at the hindfoot of the dominant leg. Conclusion . The feet of pregnant women tend to get pronated as pregnancy advances but do not reach baseline values even at 6 weeks postpartum. Pregnant women tend to bear more weight on the dominant foot with an increased static hindfoot pressure as pregnancy progresses. Levels of Evidence: Prognostic study, Level I: Prospective